PERBANDINGAN KINERJA METODE DETEKSI TEPI PADA CITRA - Kornelis Letelay (Universitas Nusa Cendana, 2019)
The results of the above analysis it is concluded that edge detection is best resulted from the user of the canny method. Edge detection using the canny method is the best edge detection because the line morphology generated by edge detection is better visible on the border of the image both on the inside and the edges of the image appear thick, vertical or horizontal lines on the front of the house is very clear when compared with the two methods above.